Health tourism development: SPA, wellness and medical treatment - Abdul Razak, Norhanim (Universiti Utara Malaysia Press, 2007)
Health tourism is a trend in the tourism market that has received considerable attention worldwide.In line with this development, the paper will explore three main segments of the health tourism market which are the health spa, the wellness attraction and the medical care. Besides these three segments, the paper will review health tourism development in Malaysia, in particular the segment that has received special attention by the officials in the country, medical treatment. As the relationship between health and travel is not a phenomenon that has just developed recently.among the main issue that will be highlighted in the paper are factors that has contributed for health tourism to emerge as one of the leading trends in the: tourism industry nowadays. An overview of health tourism concept and its development throughout the world will also be presented.Lastly, challenges and opportunities in positioning Malaysia as one of the prime health tourism destinations will also presented.